Bicuspid aortic valve endocarditis caused by Gemella sanguinis: Case report and literature review. Issue 3 (May 2019) - Maraki, Sofia; Plevritaki, Anthoula; Kofteridis, Diamantis; Scoulica, Effie; Eskitzis, Anastasios; Gikas, Achilleas; Panagiotakis, Symeon H.
Abstract: Gemella species are catalase-negative, facultative anaerobic, Gram-positive cocci, which are part of the human oral microbiome and may occasionally cause systemic infections. Infective endocarditis (IE) has been reported as the most common infection caused by Gemella species. We report the first case of IE due to Gemella sanguinis in Greece, in a patient with bicuspid aortic valve and review the available literature. The patient was successfully treated with antibiotics and aortic valve replacement.